(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1991)
The new genus Praepinacoceras with Pinacoceras damesi Mojsisovics, 1882 as type species is here described. This genus is represented by Upper Anisian to Ladinian species, having an involute, compressed shell, smooth or with thin ribs, or weak short folds or also a median spiral ridge. The suture is ammonitic with 2-4, only occasionally 6 adventitious lobes of L, U1 and U2 vey large, and numerous auxiliary elements. The suture differs from that of Pinacoceras and Eupinacoceras by its comparatively less frilled elements. The new genus, because of its stratigraphic range and its morphology is herein regarded as the ancestral form of the Fam. Pinacocnatidae.